177k views
3 votes
5(3x+9)-2x=15x-2(x-5)

User Tahamv
by
5.4k points

1 Answer

3 votes

Answer:

NO solution

Explanation:

5(3x+9)−2x=15x−2(x−5)

Step 1: Simplify both sides of the equation.

5(3x+9)−2x=15x−2(x−5)

(5)(3x)+(5)(9)+−2x=15x+(−2)(x)+(−2)(−5)(Distribute)

15x+45+−2x=15x+−2x+10

(15x+−2x)+(45)=(15x+−2x)+(10)(Combine Like Terms)

13x+45=13x+10

13x+45=13x+10

Step 2: Subtract 13x from both sides.

13x+45−13x=13x+10−13x

45=10

Step 3: Subtract 45 from both sides.

45−45=10−45

0=−35

User Andrew Berry
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.